Rancang Bangun Prototipe Alat Angkut Helikompter Berbasis Arduino - Evaristus Chandler Sunarto; Bekti Yulianti (Universitas Tarumanagara, 2019)
The development of ground support equipment in the aviation world is increasingly advanced and cannot be separated from various problems in its operation on helicopters. Ground support is a supporting tool needed to help the performance of helicopters when aircraft maintenance is carried out in the work area within the airport or while in the hangar. Some obstacles to ground support faced include holding the load, maintaining the balance of the helicopter during the towing / pushback process, in the event that the air traffic guide will delay the towing / pushback process to cross the runway to overcome this problem, the prototype of Arduino transport equipment was designed as the main controller which is controlled by an Android smartphone via a Bluetooth connection. The prototype was designed using two DC motors that function as movers and steering so that they can move forward, backward, turn and stop.from the results of testing the prototype, the maximum PWM speed conditions required are 255, the input voltage on both DC motors is 7.32 Volt will produce a 76.8 RPM rotation on motor 1 and produce a 76.4 RPM rotation on the motor 2. At speed conditions minimum PWM required is 90, then the input voltage on both DC motors is 5.77 Volt will produce 63.9 RPM rotation on motors 1 and 64.1 RPM on motor 2Perkembangan peralatan ground support di dunia penerbangan semakin maju dan tidak dapat dipisahkan dari berbagai masalah dalam pengoperasiannya pada helikopter. Ground support merupakan alat penunjang yang dibutuhkan untuk membantu kinerja dari helikopter saat dilakukan perawatan pesawat udara di area kerjanya dalam lingkup bandara maupun saat berada didalam hanggar. Beberapa kendala ground support yang dihadapi antara lain menahan beban, menjaga keseimbangan helikopter selama prosestowing/pushback berlangsung, pada kondisi notam di mana pemandu lalu lintas udara akan menunda proses towing/pushback untuk menyebrang landasan pacu, untuk mengatasi masalah tersebut, maka dirancang prototipe alat angkut dengan arduino sebagai pengendali utamayang dikendalikan dengan smartphone android melalui koneksi bluetooth. Prototipe dirancang menggunakan dua motor DC yang berfungsi sebagai penggerak dan steering agar dapat bergerak maju, mundur, berbelok dan berhenti. Dari hasil pengujian prototipe, kondisi kecepatan maksimum PWM yang dibutuhkan sebanyak 255, maka tegangan input pada kedua motor DC adalah 7,32 Volt akan menghasilkan putaran 76,8 RPM pada motor 1 dan menghasilkan putaran 76,4 RPM pada motor 2. Pada kondisi kecepatan minimum PWM yang dibutuhkan sebanyak 90, maka tegangan input pada kedua motor DC adalah 5,77 Volt akan menghasilkan putaran 63,9 RPM pada motor 1 dan 64,1 RPM pada motor 2.